2018
DOI: 10.1055/s-0037-1610379
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0)-Catalyzed Difunctionalization of 1,3-Dienes: From Racemic to Enantioselective

Abstract: 1,3-Dienes are easily accessible chemicals that participate in a series of reactions acting on the carbon–carbon double bonds. Catalytic difunctionalization of 1,3-dienes provides a wide scope of functionalized chemicals. Pd(0) catalysts provide a diverse set of principles for the creation of asymmetric catalytic reactions, which are initiated with the oxidative addition and then undergo insertion reaction with one of double bonds of the 1,3-diene to become a π-allyl palladium species that is reactive toward n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 40 publications
0
59
0
Order By: Relevance
“…In general, tertiary, secondary and primary acids were all compatible and the corresponding products could be obtained in good to excellent yields. 15 (14) were all compatible in this radical cross-coupling reaction. In all the cases, the products were obtained in excellent yields, with complete stereo-and regiocontrol.…”
Section: Entrymentioning
confidence: 74%
See 2 more Smart Citations
“…In general, tertiary, secondary and primary acids were all compatible and the corresponding products could be obtained in good to excellent yields. 15 (14) were all compatible in this radical cross-coupling reaction. In all the cases, the products were obtained in excellent yields, with complete stereo-and regiocontrol.…”
Section: Entrymentioning
confidence: 74%
“…13 Additionally, -allylpalladium complexes can be formed through oxidative addition of a Pd(0) species into an aryl or vinyl halide followed by migratory insertion into a 1,3-diene. [14][15][16][17] Methods for the generation of -allylpalladium complexes from alkyl halides or analogous electrophiles using Pd(0) (for the formation of C(sp 3 )-C(sp 3 ) bonds) have not been realized due to the reluctance of alkyl halides to undergo oxidative addition and the fast rate of β-hydride elimination of Pd-alkyl species. 18 However, recent breakthroughs in photoredox chemistry, [19][20][21] have shown that photoexcited palladium catalysts can be used to generate open-shell species from alkyl halide precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a Pd/C-catalyzed hydrogenation of alkene with H 2 balloon led to saturated spirocarbocycle 17 in 92% yield. It is noted that compounds 3a, 16, and 17 are analogs of a patented bioactive molecule for treating pain 56 , which indicates further potential application of the present method.…”
Section: Resultsmentioning
confidence: 81%
“…In this context, domino transformations involving initial carbometalation of simple alkenes or conjugated dienes and subsequent capture of the in situ generated σ-alkylmetal or π-allyl-metal species has been intensely developed for this purpose (Fig. 1a) [10][11][12][13][14][15][16] . On the other hand, as disclosed recently by the groups of Lautens [17][18][19][20] , Liang 21 , Yin 22,23 , Zhou 24 , Wu 25 , and us [26][27][28][29][30] , the application of endocyclic C=C bonds of heteroarenes as non-classic olefins has enabled a number of efficient dearomative difunctionalization reactions of indoles and furans with Pd-or Ni-catalyst 31 .…”
mentioning
confidence: 99%